Determinants of Return Stock Company Real Estate and Property Located in Indonesia Stock Exchange - Bustami, Fauzie; Heikal, Jerry (International Journal of Economics and Financial Issues, 2019)
This study estimates and analyzes the factors affecting profitability performance as well as the implications for stock returns on real estate and property sectors listed on the Indonesia Stock Exchange (IDX) during the period of 2007-2014. Of the 45 listed property companies in IDX, samples taken 23 companies. Based on the results of the research, obtained empirical findings that bring important implications in the development of the theory of profitability performance of the company associated with the factors that influence it and its implications on the stock return of the company. The study developed four groups of factors that affect the performance of the company’s profitability of interest rates, solvency, total asset turnover (TATO), and exchange rate. Factors that do not affect are Liquidity. Factors that affect the company’s stock returns are return on assets, liquidity, solvency, TATO, and exchange rate. Factors that do not affect is the interest rate. The panel data regression model to estimate the determinants of the profitability performance of real estate and property companies in Indonesia is based on three models of common effect model, fixed effect model, random effect model. Through paired pair testing for determinant of profitability performance and implication of stock return, that Random Effect model is better. For testing each model on the determinant of profitability performance. The largest fixed-effect model that is R-squared 0,532102 and adjusted R-squared 0,451120. Paired testing of two models for stock returns, that the most satisfactory fixed effect model that is R-squared 0.845078 and Adjusted R-squared 0.816351 Keywords: Interest Rate, Liquidity, Solvency, Total Asset Turnover, Exchange Rate, Profitability, Stock Return JEL Classifications: G11, G23, G32 DOI: https://doi.org/10.32479/ijefi.7445